The Influence of Super Air Jet Check-In Counter Service Quality on Passenger Satisfaction at Sultan Thaha Airport Jambi - Mayang Tri Pertiwi; Kartika Fajar Nieamah (CV. Rayyan Dwi Bharata, 2023)
In achieving the success of a company providing maximum service is one of three aspects that must be carried out by a company. Three aspects that must be prioritized are safety, security and service. A company engaged in the service sector, service user satisfaction is an absolute requirement that must be presented to gain the trust of service users. Providing satisfaction to passengers is a form of airport service with the aim that passengers enjoy comfortable, safe and timely air travel. The case that the researcher got from an article on the pre-flight service of Super Air Jet airlines, namely at the check-in counter section, is a form of passenger dissatisfaction with the services provided by the airline. The purpose of this study was to determine the effect of service quality check-in counters of Super Air Jet airlines on passenger satisfaction and how much influence this airline has on passenger satisfaction. Data collection was carried out by distributing questionnaires in quantitative research using purposive sampling techniques and a sample of 100 respondents. Using SPSS 15, Descriptive Analysis, Simple Classical Assumption Test, and Hypothesis Test were used for data analysis. Based on the results of the study, it shows that the tcount value is 8.657 ttable is 1.660, so the hypothesis Ha is accepted. This shows that the independent variable (check-in counter service quality) has an effect on the dependent variable (passenger satisfaction) on the Super Air Jet airline at Sultan Thaha Jambi Airport. The R Square value of 0.433 indicates that the variable Quality of check-in counter service has an effect of 43.3% on the variable passenger satisfaction of Super Air Jet airlines at Sultan Thaha Jambi Airport.